Employee Wellbeing: Analysis Work Life Balance, Resilience, Psychological Structure and Organizational Culture - Safariningsih, Ratna Tri Hari; Soehaditama, Josua Panatap; Arini, Dewi Ulfah; Zen, Agustian; Pramukty, Rachmat (East Asian Journal of Multidisciplinary Research, 2024)
This article specifically aims to present in-depth insights into how organizational culture, work life balance, resilience, Psychological Structure and Organizational Culture and Employee Wellbeing are applied in organizations derived from literature. The method used is qualitative by reviewing papers related to variables that exist for the duration of this paper within eight years. The presentation is related to the paper with the variables in this paper by seeing whether there have been findings in the application paper regarding the variables in this variable. The analysis highlights the pivotal roles of Work Life Balance, Resilience, Psychological Structure, and Organizational Culture in shaping Employee Wellbeing. A holistic approach that recognizes the interconnectedness of these factors is essential for creating a workplace that prioritizes and enhances overall employee wellbeing. Prioritizing these aspects not only benefits employee wellbeing but also contributes to increased productivity, retention, and a positive organizational reputation. Regular evaluation and adaptation are crucial for sustained positive impacts.